1995
DOI: 10.1097/00000542-199511000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Curves of Inhaled Nitric Oxide with and without Intravenous Almitrine in Nitric Oxide-responding Patients with Acute Respiratory Distress Syndrome

Abstract: In 6 patients with early acute respiratory distress syndrome and highly responsive to inhaled nitrix oxide, the administration of intravenous almitrine at a concentration of 16 micrograms.kg-1.min-1 induced an additional increase in Pao2. Dose response of nitric oxide was not changed by the administration of almitrine and a plateau effect was observed at inspiratory nitric oxide concentrations of 1.5 ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 31 publications
4
51
1
Order By: Relevance
“…Similar findings have been reported in studies by PUYBASSET et al [12] and ADATIA et al [22]. NO doses of as little as 1-2 ppm have been shown to be sufficient for optimal treatment of pulmonary hypertension in ARDS patients [9][10][11]. In contrast with these, as well as with the present study, the optimal NO dose in terms of pulmonary vasodilation was found to be as high as 100 ppm by GERLACH et al [13].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar findings have been reported in studies by PUYBASSET et al [12] and ADATIA et al [22]. NO doses of as little as 1-2 ppm have been shown to be sufficient for optimal treatment of pulmonary hypertension in ARDS patients [9][10][11]. In contrast with these, as well as with the present study, the optimal NO dose in terms of pulmonary vasodilation was found to be as high as 100 ppm by GERLACH et al [13].…”
Section: Discussionsupporting
confidence: 92%
“…The present study further confirms that low NO doses, i.e. in the 0.5-5 ppm range, progressively improve Pa,O 2 in ARDS patients [8][9][10][11][12]. In addition, the results indicate that the Pa,O 2 response to NO doses >5 ppm varies between patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the observation that shunt flow further increased with the U-46619 infusion contrasts with the common belief that increases in pulmonary artery pressure are usually associated with an improvement in V'/Q' matching. In patients with ARDS, it was recently shown that combining the inhaled vasodilator NO with the intravenously applied vasoconstrictor, almitrine, potentiated an improvement in gas exchange and reduction of shunt flow, as with either NO or almitrine applications [35]. Because almitrine selectively constricts pulmonary arteries and not pulmonary veins [36], it is unlikely that almitrine increases the hydrostatic capillary pressure, but this might be responsible for the U-46619-induced shunt flow, probably as a result of a greater proportion of the lungs in zone 3.…”
Section: Discussionmentioning
confidence: 99%